Assessment of causal effects of physical activity on neurodegenerative diseases: A Mendelian randomization study - Peng-Fei Wu; Hui Lu; Xiaoting Zhou; Xuchen Liang; Ruizhuo Li; Wan Zhang; Danyang Li; Kun Xia (Elsevier, 2021)
Background: Physical activity has been hypothesized to play a protective role in neurodegenerative diseases. However, effect estimates previously derived from observational studies were prone to confounding or reverse causation. Methods: We performed a two-sample Mendelian randomization (MR) analysis to explore the causal association of accelerometer-measured physical activity with 3 common neurodegenerative diseases: Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS). We selected genetic instrumental variants reaching genome-wide significance (p < 5 × 10−8) from 2 largest meta-analyses of about 91,100 UK Biobank participants. Summary statistics for AD, PD, and ALS were retrieved from the up-to-date studies in European ancestry led by the international consortia. The random-effect, inverse-variance weighted MR was employed as the primary method, while MR pleiotropy residual sum and outlier (MR-PRESSO), weighted median, and MR-Egger were implemented as sensitivity tests. All statistical analyses were performed using the R programming language (Version 3.6.1; R Foundation for Statistical Computing, Vienna, Austria). Results: Primary MR analysis and replication analysis utilized 5 and 8 instrumental variables, which explained 0.2% and 0.4% variance in physical activity, respectively. In each set, one variant at 17q21 was significantly associated with PD, and MR sensitivity analyses indicated them it as an outlier and source of heterogeneity and pleiotropy. Primary results with the removal of outlier variants suggested odds ratios (ORs) of neurodegenerative diseases per unit increase in objectively measured physical activity were 1.52 for AD (95% confidence interval (95%CI): 0.88-2.63, p = 0.13) and 3.35 for PD (95%CI: 1.32-8.48, p = 0.01), while inconsistent results were shown in the replication set for AD (OR = 1.06, 95%CI: 1.01-1.12, p = 0.02) and PD (OR = 0.99, 95%CI: 0.88-0.12, p = 0.97). Similarly, the beneficial effect of physical activity on ALS (OR = 0.51, 95%CI: 0.29-0.91, p = 0.02) was not confirmed in the replication analysis (OR = 0.96, 95%CI: 0.91-1.02, p = 0.22). Conclusion: Genetically predicted physical activity was not robustly associated with risk of neurodegenerative disorders. Triangulating evidence across other studies is necessary in order to elucidate whether enhancing physical activity is an effective approach in preventing the onset of AD, PD, or ALS.